Enhancement of therminol-based nanofluids with reverse-irradiation for medium-temperature direct absorption solar collection. (September 2020) - Wang, K.; He, Y.; Kan, A.; Yu, W.; Wang, L.; Wang, D.; Liu, P.; Xie, H.; She, X.
Abstract: The nanofluids-based direct absorption solar collector (DASC) is considered as the next-generation solar collection technology due to its high photo-thermal conversion efficiency. However, the key challenges for its development are the large temperature gradients inside nanofluids and the agglomeration of nanoparticles. To address these issues, this paper proposes to apply solar irradiation at the bottom surface of the DASC (i.e. reverse irradiation) rather than at the top surface, which changes the heat transfer mode from heat conduction to heat convection. Experimental test is carried out for the first time for medium-temperature solar collection ( 150 °C), where titanium nitride is selected as nanoparticles and therminol as base fluid. The experimental results show that reverse irradiation contributes to a uniform temperature distribution in nanofluids and results in a 36.4% higher photo-thermal conversion efficiency compared with the top irradiation; the maximum efficiency can reach up to 80%. What's more, the response time for nanofluids to achieve a steady-state temperature is shortened by 55.6%. One week test shows that reverse irradiation significantly improves the stability of nanofluids and mitigates the agglomeration of nanoparticles. Therefore, it can be concluded that the reverse irradiation DASC is a high-efficient, a fast-response and a long lifetime technology for solar collection. Graphical abstract: Reverse irradiation is an effective method for direct absorption solar collectors to significantly improve the photo-thermal conversion efficiency of nanofluids, shorten the response time to achieve a target temperature and enhance the stability of nanofluids. Image 1 Highlights: Therminol-based nanofluids are studied for reverse-irradiation direct absorption solar collector (RI-DASC). The RI-DASC is not only energy-efficient but also fast response to solar irradiation. The photo-thermal conversion efficiency is improved up to 80%. The response time for nanofluids to achieve a steady-state temperature is shortened by 55.6%.